How does childhood family background affect trajectories to adulthood? Evidence from China - Dianxi Wang (Comparative Population Studies (CPoS), 2022)
Existing research has found that since the late 1960s, the pathway to adulthood in Western countries has undergone complex changes, but few studies have investigated such changes and the effect of childhood family background on the transition to adulthood within the Chinese context. This study aims to examine the role of childhood family background in the transition to adulthood among Chinese youth born between 1930 and 1979. We identified four clusters of trajectories to adulthood in both the family and occupational domain. In the occupational domain, more than a quarter of respondents fall into the cluster of high studies & non-agricultural employment and in the family domain, nearly one-third of the sample follows the clusters of marriage & one child and staying single longer, reflecting the increasing diversity and delay in transition to adulthood. Parents' occupations during childhood had a significant effect on both occupational trajectory and family trajectory. Higher occupational status of parents delayed the transition to adulthood, while lower occupational status of parents promoted the transition to adulthood. Family economic status during childhood had a greater effect on occupational trajectories. Young people with worse family financial situations in childhood were more likely to enter the labour market earlier, while those with better family financial situations were more likely to receive long-term education and delay entering the workforce. The mother's religious belief had a more significant effect on the family life course. Youths with non-religious mothers were more likely to fall into the unmarried or childless cluster. In the Chinese context, the political status of the father played an important role in adult transition. A father's Communist party membership in childhood was positively correlated with the likelihood that individuals would follow the pattern of trajectory to adulthood characterised by long-term education.
urn:nbn:de:bib-cpos-2022-11en8
Keywords: 300; Transition to adulthood; Life course; Childhood family background